2013
DOI: 10.1590/s1415-43662013001100014
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of rainfall and erosion under natural conditions of land use in semiarid regions

Abstract: The characteristics of rainfall can provide important information for management and land use may also minimize the water erosion problems. This study was carried out to evaluate soil and water loss in erosion plots with different coverage, and the interference of natural rainfall characteristics on these processes. The experiment was carried out during the rainy season in the years of 2009 and 2010, on three erosion plots, each of 20 m 2 , and under different land use conditions: native 'caatinga', thinned 'c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 16 publications
0
12
0
3
Order By: Relevance
“…Climate change is expected to substantially influence precipitation distribution and amounts (Zittis et al, 2017). Studying of temporal distribution of heavy rainfall events is very important to evaluate the amount of runoff and soil erosion and also can modify water availability, groundwater recharge and hydroelectric production (De Lima et al, 2013;Yu et al, 2018). Several studies on spatial and temporal variations of precipitation concentration have been undertaken all over the world to study the statistical structure of daily precipitation according to its concentration during the year and evaluate the heaviest precipitation events (Monjo and Martin-Vide, 2016;Yeşilırmak and Atatanir, 2016;Royé and Martin, 2017;Zheng et al, 2017;Serrano-Notivoli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is expected to substantially influence precipitation distribution and amounts (Zittis et al, 2017). Studying of temporal distribution of heavy rainfall events is very important to evaluate the amount of runoff and soil erosion and also can modify water availability, groundwater recharge and hydroelectric production (De Lima et al, 2013;Yu et al, 2018). Several studies on spatial and temporal variations of precipitation concentration have been undertaken all over the world to study the statistical structure of daily precipitation according to its concentration during the year and evaluate the heaviest precipitation events (Monjo and Martin-Vide, 2016;Yeşilırmak and Atatanir, 2016;Royé and Martin, 2017;Zheng et al, 2017;Serrano-Notivoli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Three different groups of events were formed for the watershed RC. The formation of different groups express high temporal variability of events, which is a characteristic of the region (LIMA et al, 2013). The rainfall characteristics affected the grouping results of the watershed RC, with the rainfall in group 1 presenting lower rainfall, I30 and erosivity, however, presenting the highest average of 5-day accumulated precipitation (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…However, few studies assessed the effects of changes in land use in the Brazilian semiarid on hydrological and sedimentological processes, which cause irreparable damages, such as siltation and eutrophication of water bodies. The obtaining of a better correlation between erosivity and soil losses is limited by the high variability and low information on precipitation physical characteristics (ALBUQUERQUE et al, 2005;LIMA et al, 2013;WESTER;WASKLEWICZ;STALEY, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Zheng [11] intensity in relation to sheet erosion, Spain (I 30 ) Marques et al [12] rainfall-runoff relationships in cropping lands, Queensland, Australia (I 30 ) Freebairn et al [13] Brasil et al [4] Indices calculated over short time periods are to be found in many other works, including I 5 and I 15 [20]; I 5 [21]; I 10 and I 30 [22]; and I 6 , I 20 , and I 30 [23].…”
Section: Area Of Application Of I 30 and Related Indexes Referencementioning
confidence: 98%